Penguatan Literasi Keuangan dan Digitalisasi Akuntansi bagi UMKM melalui Kolaborasi Internasional - Desy Nur Pratiwi; Supot Rattanapun; Yuwita Ariessa Pravasanti; Muhammad Tho’in; Maulida Nur Khasanah; Wildan Fauzan (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2026)
This community service program aims to understand the management of MSMEs in Thailand and the effectiveness of accounting digitalization in strengthening financial literacy to adapt to technological developments. This activity was carried out in several stages: preparation, core, and closing. The initial stage began with identifying the MSME partners' problems. In the second stage, the community service team conducted outreach and training, and in the third stage, an evaluation of the activity was conducted. The results of this community service activity indicate that the training made a significant contribution to strengthening MSMEs' financial literacy. This can be seen in the ability and implementation of the importance of separating personal and business finances, as well as the importance of preparing business financial reports. Furthermore, this activity encouraged MSMEs to consistently maintain financial records using digital applications. This change in attitude among MSME partners has resulted in increased confidence in accessing formal financing and in conducting ongoing business evaluations for long-term sustainability. Keywords: Accounting Digitalization, Financial Literacy, MSMEs